A onipresença processual dos atos de investigação como sintoma biopolítico - Sampaio, André Rocha (2016)
Around 2008 there was a series of reforms in the brazilian Code of Criminal Procedure, including the one that changed the text of Article 155. The original text of the Bill provided for the use only of the acts produced in contradictory court for building the judicial conviction. However, based on arguments of authoritarian nature, the text approved enables the juditial conviction also in acts of investigation, as long as not exclusively. Despite the text continues assigning greater value to acts of proof compared to research acts - as it is possible sentencing only based on those and not on these – it has been commonplace in forensic practice the widespread use of research actions, subtly standing to not grossly defying the norm in question. Factors that support this systemic re-accommodation, this slide between the designed, approved and implemented has ramifications far beyond the legal boundaries. The political, the social, the anthropological and the historical are just some of the fields in which it is possible to see, each in its own way, authoritarianism spread founding what is meant today by a "biopolitics of bodies". In this path, the criminal case is handled by its obverse: from a reducer instrument of political power it metamorfoses itself into certain criminal policy enforcement tool, backed only in fear of unreasonable / irrational nature. An analysis of the main institutions involved in this process, namely the judicial police and the judge, only corroborate to unveil the ingenuity or trick in keeping the current configuration of the relationship of the court judgment to the preliminary acts of investigation. Therefore, it became imperative to find ways to dam the authoritarian impulses that blend together the systemic gaps, going beyond the physical exclusion of acts of investigation in the judicial phase - taking into account the previous separation between judge of guarantees and judge of the process and the distinction between repeatable and unrepeatable acts of research - but going beyond, targeting the possibility of maximum compression of the preliminary phase, which is feasible before the provisional arrest request situation during the investigative phase. By the presented model, the statement would have at least their repeatable acts exclusively produced in contradictory court, reducing the possibilities of sentence contamination with the acts arising from the previous phase.